Transgender and non-binary prisoners' experiences in England and Wales - Suhomlinova, Olga; O'Shea, Saoirse Caitlin (Emerald Publishing Limited, 2024)
Few studies have explored the lives of imprisoned transgender women and none consider non-binary prisoners. Transgender and Non-Binary Prisoners' Experiences in England and Wales fills this gap by delving deep into their ordeals. Drawing on a three-year project of correspondence with nineteen trans women and four non-binary persons incarcerated in men's prisons as well as a critical analysis of the Prison Service policies and practices, Olga Suhomlinova and Saoirse Caitlin O'Shea bring to light the realities of these lives, in the prisoners' own words. Rich in inimitable detail, Transgender and Non-Binary Prisoners' Experiences in England and Wales documents the struggles against harassment and abuse, the challenges of access to transgender healthcare and feminine items, and the complexities of relationships with other prisoners and staff, revealing the strength of character required to maintain individual identity in a totalising institution. The participants' introductions and "Life in the Day" essays also offer a close-up of what it takes to be a trans prisoner. Steeped in unique empirical evidence, Transgender and Non-Binary Prisoners' Experiences in England and Wales acts as a timely intervention, voicing the concerns of these marginalised groups and suggesting ways to improve their conditions of confinement. The book is of interest to students and scholars in penology/criminology, sociology, and gender/transgender studies, prison policy makers and practitioners, and human rights activists.